Proceedings of the International Conference on Advances in Energy, Environment and Chemical Engineering 2015
DOI: 10.2991/aeece-15.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Cadmium Tolerance on the Growth Characteristics of Industrial Hemp (Cannabis sativa L.) in China

Abstract: Abstract.The effects of different concentrations of cadmium (Cd) on the growth physiological parameters of industrial hemp, including growth, the photosynthetic characteristics, the chlorophyll fluorescence and so on, were studied with hydroponic greenhouse experiments. The results showed that with the increase of Cd concentration, the levels of chlorophyll a, chlorophyll b and carotenoids in hemp leaves decreased, and the decreasing rates were in the following order: carotenoid> chlorophyll b>chlorophyll a. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Considering the significant increase in intercellular CO2 concentration in both poplar clones, but differential gs response following Cd exposure, our results suggest different mechanisms (stomatal and/or mesophyll impairments) are involved in Cd-induced reduction of photosynthetic activity in the studied poplars. Reduction of net photosynthetic rate due to mesophyll limitations has been observed in other woody (Salicaceae -Vassilev et al 2005) and herbaceous (Tang et al 2015) species exposed to Cd. However, the increase of intercellular CO2 levels observed in both clones (regardless of gs) suggests inhibition of Calvin cycle enzymes rather than PSII activity in the tested clones (Pajević et al 2009).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 77%
“…Considering the significant increase in intercellular CO2 concentration in both poplar clones, but differential gs response following Cd exposure, our results suggest different mechanisms (stomatal and/or mesophyll impairments) are involved in Cd-induced reduction of photosynthetic activity in the studied poplars. Reduction of net photosynthetic rate due to mesophyll limitations has been observed in other woody (Salicaceae -Vassilev et al 2005) and herbaceous (Tang et al 2015) species exposed to Cd. However, the increase of intercellular CO2 levels observed in both clones (regardless of gs) suggests inhibition of Calvin cycle enzymes rather than PSII activity in the tested clones (Pajević et al 2009).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 77%
“…2E) and increase of NPQ (Fig. 2F) showed that the damage to PSII induced by a high Cd dose was not enough to cause the photoinactivation, with PSII being protected by an effective dissipation mechanism of heat to avoid the photoinhibition at the reaction centres (Li et al 2015; Tang et al 2015), these findings are corroborated by Ge et al (2015).…”
Section: Discussionmentioning
confidence: 75%
“…The effects of Cd stress on chlorophyll fluorescence parameters ( Fv/Fm , qP , ETR and NPQ ) (Fig. 2) may indicate an inhibition of the activity of PSII, resulting in changes in the photosynthetic rate of plants (Pajević et al 2009; Tang et al 2015). The reduction of Fv/Fm values (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The higher YII values indicate strong PSII activity and higher energy conversion to photochemical products. Lower YII values indicate closed reaction center, low absorption and conversion (Yang et al, 2015). In our study, the increased YII values at lower concentration of Pb 2+ treatment could be correlated to the culture tolerance.…”
Section: Discussionmentioning
confidence: 99%